Study on characterization of chalcone synthase gene from \(Pueraria lobata\) and \(Pueraria mirifica\) in Vietnam - Thu Hue, Huynh Thi; Phuong, Nguyen Minh; Canh, Nguyen Xuan (Academia Journal of Biology, 2021)
Two species of genus Pueraria ((Pueraria lobata (synonym: Pueraria montana var. lobata) and Pueraria mirifica (synonym: Pueraria candollei var. mirifica)) are traditional plants used in medicine since ancient times. These plants have been used and became commercially crucial indigenous medicinal plants. Currently, both roots and flowers of P. mirifica are used as a dietary supplement and functional food for women because of their rich source of phytoestrogen and nutrition. However, little information of genes on both species of Pueraria genus (P. lobata and P. mirifica) are known in Vietnam. The purpose of this research is to support more understanding about Chalcone synthase (CHS) genes by determining and sequence analyzing an encoding region of CHS genes that were isolated from P. lobata and P. mirifica. The full-length open reading frame (ORF) sequence CHS was identified with 1170 bp which encodes 389 amino acids by Sanger sequencing. The isolated CHS gene of P. lobata has no difference in sequence with CHS reported on GenBank (D10223.1), whereas a difference of 26 nucleotide positions in CHS sequence of P. mirifica compared with the published gene sequence (JQ409456.1) as consequential having 97.78% genetic similarity. The CHS genes sequence of P. lobata and P. mirifica are homologous with 98.4% because of having 19 nucleotide differences. Chalcone-stilbene synthase N-C terminal, PLN03173, CHS-like, BH0617, fabH are some important domains predicting the CHS genes. Especially, the family signature ‘GVLFGFGPGLTI’ motif of CHS gene as a part of the active-site scaffold contributes to decide the product of cyclization reactions performing the stereochemistry of cyclization which was also observed in P. lobata and P. mirifica, but it was not included for all members in Fabaceae family. With in sillico analysis, the P. lobata and P. mirifica CHS sequences have highly conserved regions to maintain their structure and function, so that it needs further studies to clarify these points.